Effect of Ground Touching on the Drag and Spreading Power of the Otterboard during a Bottom Trawling Operation - Ibrahim, Sakri (1988)
Trawling at five different speeds was carried out to estimate the ground spread and the ground drag and friction. The ground drag and friction increases with towing speed at almost the same rate as the actual drag force of the otterboard. The ground spread is only significant at low speeds. When speed increases, the ground spread gradually decreases. The ground spread can be used to advantage only before the speed reaches around 1.41 mis, after which the ground drag and friction will become higher and thus nulify all the spreading advantages provided by the ground spread. From this experiment, it may also be deduced that a flat type otterboard with a small "point of contact" (high aspect ratio) is the most suitable otterboard for bottom trawling operations.